Phagochytosis Activity Test of Red Ginger and Angkak Combination Extract by Carbon Clearance Method - Fajar Nugraha; Halim Halim; Hariyanto IH; Andhi Fahrurroji; Desy Siska Anastasia (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Red ginger (Zingiber officinale Roscoe var. rubrum) and angkak (Oryza sativa) are used in traditional chinese medicine to improve body health. Both are known to have immunostimulatory activity that increases phagocytic activity of macrophage. This study aims to determine the phagocytic activity of the combination extract of red ginger and angkak using carbon clearance method. Combination of red ginger and angkak (7:3) was kinetically macerated in ethanol 96%. Twenty white mice were divided into 5 groups, such as control group (CMC-Na 0.5%), positive control (Levamisole 2.5 mg/kgBB), and three experiment group that was given red ginger extract (105 mg/kgBB), angkak extract (105 mg/kgBB), and combination extract of red ginger-angkak (150 mg/kgBB). All treatments were given orally for sevendays, consecutively. The phagocytosis index (IF) value was determined on day 8 by injecting carbon intravenously and immunostimulant activity was shown if IF>1. The highest IF value of three extracts was shown by combination extract (1.2489±0.0261) compared to red ginger and angkak extract, mentioned 1.2030±0.0448 and 1.0537±0.0254, respectively. Moreover, the IF values of combination extract and red ginger were significantly (p<0.05) different compared to the control group of CMC-Na (IF=1). However, it is significantly (p>0.05) lower compared to the levamisole group (1.5187±0.0534). It could be concluded that the combined extract of red ginger-angkak showed the greatest phagocytic activity against male white mice compared to extract of red ginger and angkak itself.